Mejora de la experiencia de usuario de sistema ERP SAP con plataforma y aplicaciones basadas en el ERP SAP para la empresa Marino S.A. 2019 - 2020 - Chavez Callupe, Paul Jorge (2022)
The present research work is a work that represents the end of a journey in the search for an improvement not only at a technological level but, to a greater extent, an impact at a business level that has managed to reveal critical internal and external aspects that have allowed identifying the points of improvement that every company in the fishing sector should take into consideration to make the leap towards digital transformation. As part of this search for change, a company called MARINO S.A. (a fishing industry company) has been considered as the company subject to research and an IT consulting company (systems implementation company) as two relevant subjects because this work is based on real information (considering certain modifications to protect sensitive information), which allows the analysis, understanding and interpretation of the information collected can provide a clearer picture regarding the implementation of an ERP SAP system and its respective improvements applied. (UNAS, 2022) In this way, the implementation of an ERP SAP S/4 HANA system represents a technological breakthrough and a milestone for companies that contemplate the need to experiment and implement changes in the way of working and in the way of managing one of their the most important elements when making important decisions, redistributing and equating human and financial capital and carrying out internal projects with a view to more reliably calculated scenarios. This element is called “Data”. Under this explanation, it is contemplated that the reader can create their own conclusions and be able to discern the change brought about by the work of a team of consultants, direct and indirect users and the entire management team to give birth to a new way of organizing and promoting the progress of companies today.